Cardioprotecive Properties of Known Agents in Rat Ischemia-Reperfusion Model Under Clinically Relevant Conditions: Only the NAD Precursor Nicotinamide Riboside Reduces Infarct Size in Presence of Fentanyl, Midazolam and Cangrelor, but Not Propofol - Xiao, Yang; Phelp, Philippa; Wang, Qian; Bakker, Diane; Nederlof, Rianne; Hollmann, Markus W.; Zuurbier, Coert J. (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardioprotective strategies against ischemia-reperfusion injury (IRI) that remain effective in the clinical arena need to be developed. Therefore, maintained efficacy of cardioprotective strategies in the presence of drugs routinely used clinically (e.g., opiates, benzodiazepines, P2Y12 antagonist, propofol) need to be identified in preclinical models. Methods: Here, we examined the efficacy of promising cardioprotective compounds (fingolimod (Fingo), empagliflozin (Empa), melatonin (Mela) and nicotinamide riboside (NR)) administered i.v. as bolus before start ischemia. Infarct size as percentage of the area of risk (IS%) was determined following 25 min of left ascending coronary (LAD) ischemia and 2 h of reperfusion in a fentanyl-midazolam anesthetized IRI rat model. Plasma lactate dehydrogenase (LDH) activity at 30 min reperfusion was determined as secondary outcome parameter. Following pilot dose-response experiments of each compound (3 dosages, n=4-6 animals per dosage), potential cardioprotective drugs at the optimal observed dosage were subsequently tested alone or in combination (n=6-8 animals per group). The effective treatment was subsequently tested in the presence of a P2Y12 antagonist (cangrelor; n=6/7) or propofol aesthesia (n=6 both groups). Results: Pilot studies suggested potential cardioprotective effects for 50mg/kg NR (p=0.005) and 500 µg/kg melatonin (p=0.12), but not for Empa or Fingo. Protection was subsequently tested in a new series of experiments for solvents, NR, Mela and NR+Mela. Results demonstrated that only singular NR was able to reduce IS% (30 ± 14% vs 60 ± 16%, P=0.009 vs control). Mela (63 ± 18%) and NR+Mela (47 ± 15%) were unable to significantly decrease IS%. NR still reduced IS in the presence of cangrelor (51 ± 18% vs 71 ± 4%, P=0.016 vs control), but lost protection in the presence of propofol anesthesia (62 ± 16 % vs 60 ± 14 %, P = 0.839 vs control). LDH activity measurements supported all IS% results. Conclusion: This observational study suggests that NR is a promising cardioprotective agent to target cardiac ischemia-reperfusion injury in clinical conditions employing opioid agonists, benzodiazepines and platelet P2Y12 inhibitors, but not propofol.